Remembrance : selected correspondence of Ray Bradbury - Bradbury, Ray, 1920-2012 (Simon & Schuster, 2023)
Told through letters from his late teens to his ninth decade, this collection shows the iconic author's progression through life as he knew it, illuminating his enduring legacy as a storyteller, novelist and space-age visionary whose works turned into popular adaptations for stage, film and television.